Do Maternal Sociodemographic Factors Explain Race/Ethnic Differences in Neonatal Anthropometry in Low Risk Women? [14N]. (May 2018) - Lambert, Calvin; Pugh, Sarah; Liu, Aiyi; Ayele, Fasil Takola; Grantz, Katherine
Abstract : INTRODUCTION: Racial/ethnic differences in birthweight exist. It is unclear to what extent these differences are due to correlates of social disadvantage. Our objective was to evaluate whether relationships between maternal race/ethnicity and neonatal anthropometry varied by maternal socio-demographic characteristics in a cohort of healthy, low-risk women. METHODS: In a prospective cohort of 1, 645 low-risk singleton pregnancies included in the NICHD Fetal Growth Studies (2010-2013), neonatal anthropometry was measured by trained personnel using a standard protocol. Sociodemographic characteristics were ascertained by interview and included full-time employment/student status (yes/no), marital status, health insurance source (private/managed vs Medicaid/other), income, and education. Separate generalized linear models were used to test the effect of race/ethnicity and the combined effect of race/ethnicity and sociodemographic characteristics (with two-way interaction terms) on neonatal anthropometry adjusting for days from birth (except birthweight) infant sex, and maternal characteristics: age, height, pre-gravid weight, parity, and the other sociodemographic factors. RESULTS: Mean birthweight, and neonatal weight, length, head circumference and abdominal circumference at examination differed significantly by race (p<0.001 for all comparisons). No statistically significant interactions occurred between race/ethnicity and full-time employment/student status, marital status, insurance, or education in association with birthweight, neonatal weight, length, or head or abdominal circumference at examination. The interaction of income with race/ethnicity was marginally significant for abdominal circumference (p=0.027). There were no significant interactions of income with other neonatal parameters and the observed significance may have occurred by chance (1 of 25 models). CONCLUSION: Racial/ethnic differences in neonatal anthropometry were not explained by sociodemographic factors in low-risk women.